2007
DOI: 10.4315/0362-028x-70.1.200
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Peroxyacetic Acid Formulation as an Antimicrobial Intervention To Reduce Levels of Inoculated Escherichia coli O157:H7 on External Carcass Surfaces of Hot-Boned Beef and Veal

Abstract: The efficacy of a peroxyacetic acid formulation (POAA) at reducing Escherichia coli O157:H7 contamination on external carcass surfaces of hot-boned beef and veal with a commercial spray apparatus was determined. Hot-boned external carcass surfaces were inoculated with either a high dose (10(6) CFU/cm2) in fresh bovine feces or with a low dose (10(3) CFU/cm2) in diluent of laboratory-cultured E. coli O157:H7. Treatments included a water wash, a POAA (180 ppm) wash, or a water plus POAA wash. Samples were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 12 publications
0
14
1
Order By: Relevance
“…When counts were below the detection limit (2.0 log CFU/20 cm 2) of the method, a number between 0 and the lowest detection limit was used to facilitate the data analysis. differs from results reported by Penney et al (26), who found greater reductions after PAA compared with water applica tion. In contrast, King et al (18) achieved greater reductions of E. coli 0157:H7 and Salmonella Typhimurium with a water wash than with PAA.…”
Section: Analysis Of High-level-inoculum Strip Loin Piecescontrasting
confidence: 91%
“…When counts were below the detection limit (2.0 log CFU/20 cm 2) of the method, a number between 0 and the lowest detection limit was used to facilitate the data analysis. differs from results reported by Penney et al (26), who found greater reductions after PAA compared with water applica tion. In contrast, King et al (18) achieved greater reductions of E. coli 0157:H7 and Salmonella Typhimurium with a water wash than with PAA.…”
Section: Analysis Of High-level-inoculum Strip Loin Piecescontrasting
confidence: 91%
“…However, supplementary hot water spraying (95 °C) did not further enhance the efficacy (Castillo et al, 1999a). Besides, in the study of Phebus et al (1997) Occasionally, the antibacterial activity of water spraying in combination with chemicals as ASC, chlorine, H 2 O 2 , ozone, peroxyacetic acid, saponin, TSP or commercially available preparations was investigated on inoculated beef carcass surface parts (Cabedo et al, 1996;Castillo et al, 1999b;Castillo et al, 2003;Cutter, 1999;Gorman et al, 1995b;Marshall et al, 2005;Penney et al, 2007). The different chemicals were mainly investigated in only one single study and under laboratory conditions.…”
Section: Combinations Of Physical and Chemical Interventionsmentioning
confidence: 99%
“…Furthermore, a lot of research has been carried out on the effectiveness of various commercially available preparations, (Cutter and Siragusa, 1995;Reagan et al, 1996;Bell et al, 1997;Dorsa et al, 1997;Cutter, 1999;Cutter and Rivera-Betancourt, 2000;Bosilevac et al, 2004;Gill and Badoni, 2004;King et al, 2005;Algino et al, 2007;Penney et al, 2007;Arthur et al, 2008;Pearce and Bolton, 2008;Kalchayanand et al, 2009).…”
Section: Other Chemical Treatmentsmentioning
confidence: 99%
“…This chemical received approval from FSIS -USDA for use in beef carcass decontamination systems. On the other hand, acidified sodium chlorite, electrolyzed water or peroxyacetic acid mainly yielded reductions below one order of magnitude (Algino et al, 2007;Arthur et al, 2008;Gill and Badoni, 2004;King et al, 2005;Penney et al, 2007). Under commercial conditions, H 2 O 2 and ozone reduced naturally occurring bacteria on carcasses by 1.0-1.1 and 1.1-1.3 log CFU cm -2 , respectively (Reagan et al, 1996;Algino et al, 2007).…”
mentioning
confidence: 99%